Patient doses in a biplane angiography system. (September 2016) - Andres, C.; Agulla, M.; Torres, R.; Perez-Garcia, H.; del Castillo, A.; Miguel, D.; de Frutos, J.; Alonso, D.; Perez, C.; Gomez, M.
Abstract : Introduction: The development of biplane angiography systems is a huge advance in neurointerventional procedures but also a possible increase in patient doses. Purpose: This work aims to evaluate dosimetric parameters associated with doses to patients during the first year of use of a biplane angiography system Materials and methods: The angiography system analyzed was a Siemens Artist Zee biplane. Intervention's parameters were obtained by means of the radiation dose structured report. 358 interventions were analyzed according to the following parameters: radiation time, skin dose, dose at interventional reference point and dose-area product (DAP). Average (±95% CI) and the maximum values of each data series were obtained Results: On average, each intervention needed 39:03 ±4:05 min of radiation time (71.2% due to plane A) with a maximum value of 7:12:34 h. DAP was, on average, 136 ±11 Gycm 2 (80.8% due to plane A) with a maximum of 1435 Gycm 2 . Patient skin dose was, on average, 0.55 ± 0.07 Gy for plane A and 0.51 ± 0.09 Gy for plane B with maximum values of 4.24 Gy (plane A) and 4.20 Gy (plane B) Conclusion: Patient doses from a biplane angiography system are evaluated. Results show patient dose values significantly greater than those obtained in other interventional procedures. DAP and irradiation time were considerably higher for the plane A (usually craniocaudal). However, the skin dose for both planes shows similar values. Disclosure: The authors declare that they have no conflicts of interest.